2021
DOI: 10.1186/s12957-021-02349-5
|View full text |Cite
|
Sign up to set email alerts
|

Iliosacral Bone Tumor Resection Using Cannulated Screw-Guided Gigli Saw - A Novel Technique

Abstract: Background Adequate margins are technically difficult to achieve for malignant tumors involving the sacroiliac joint due to limited accessibility and viewing window. In order to address the technical difficulties faced in iliosacral tumor resection, we proposed a technique for precise osteotomy, which involved the use of canulated screws and Gigli saw (CSGS) that facilitated directional control, anteroposterior linkage of resection points and adequate surgical margins. The purpose of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Indeed, iliosacral resection without reconstruction could serve as an effective treatment option for pelvic type I-IV tumors (1). Gordon et al reported on 16 patients who underwent resection of the iliosacral joint; all 4 patients who underwent reconstruction required walking aids, whereas among the 12 patients who did not undergo reconstruction, 9 were able to walk without aids (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, iliosacral resection without reconstruction could serve as an effective treatment option for pelvic type I-IV tumors (1). Gordon et al reported on 16 patients who underwent resection of the iliosacral joint; all 4 patients who underwent reconstruction required walking aids, whereas among the 12 patients who did not undergo reconstruction, 9 were able to walk without aids (20).…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al. reported on 16 patients who underwent resection of the iliosacral joint; all 4 patients who underwent reconstruction required walking aids, whereas among the 12 patients who did not undergo reconstruction, 9 were able to walk without aids ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described in their retrospective review on 15 patients who underwent resections for primary tumors of pelvis or sacrum using canulated screws and Gigli saw to facilitate the directional control of the osteotomy, Ji et al found an ideal resection accuracy with a high likelihood of negative margin resections. This effective method allows a precise control of the osteotomy and allow achievement of planned surgical margins and may be used for this indication [ 29 ]. The good functional and oncological outcomes of pasteurized autograft reconstruction after resection of periacetabular malignant bone tumors was demonstrated by Guo et al with a relatively low incidence of complications.…”
Section: Discussionmentioning
confidence: 99%